Kuin tarpeeton mä oisin. - Tuominen, Jamppa, 1949-1998; CBS Records Oy ([Kustannuspaikka tuntematon] : CBS Records, 1982)
2 kappaletta.
Jamppa Tuominen (lauluääni).
Keywords: Tuominen, Jamppa, -- 1949-1998 -- singlet; iskelmät